#### Answer

{3}

#### Work Step by Step

7(3x - 2) + 5 = 6(2x - 1) + 24
Step 1 : Use distributive property
7.3x - 7.2 + 5 = 6.2x - 6 + 24
Multiply
21x - 14 + 5 = 12x -6+24
Solve
21x - 9 = 12x + 18
Step 2 : Collect variable terms on one side and constants on the other side.
subtract 12x from both the sides
21x -9 -12x = 12x + 18 - 12x
9x - 9 = 18
Add 9 on both the sides
9x - 9 + 9 = 18 + 9
9x = 27
Divide both the sides by 9
$\frac{9x}{9}$ = $\frac{27}{9}$
x = 3
Now we check the proposed solution, 3 , by replacing x with 3 in the original equation.
Step 1: the original equation 7(3x - 2) + 5 = 6(2x - 1) + 24
Step2: Substitute 3 for x
7(3.3 - 2) + 5 = 6(2.3 - 1) + 24
Step 3: Simplify
7(9 -2) +5 = 6(6-1) + 24
7(7) + 5 = 6(5) + 24
Multiply 7(7) = 49 , 6(5) = 30
49 + 5 = 30 + 24
Solve
54 = 54
Since the check results in true statement, we conclude that the solution set of the given equation is {3}